Characterization and evaluation of native rhizobacteria isolated from Meloidogyne incognita-infected tomato (Solanum lycopersicum) - MANJUNATHA T GOWDA; RADHA PRASANNA; ADITI KUNDU; V S RANA; GAUTAM CHAWLA (The Indian Journal of Agricultural Sciences, 2023)
Three native rhizobacteria, IRh9, IRh10 and IRh15, were isolated from nematode-infected tomato (Solanum lycopersicum L.) rhizosphere were characterized and evaluated for their efficacy against root-knot nematode (RKN), Meloidogyne incognita infecting tomato crop under pot conditions in the protected structure environment during 2020–21 at Centre for Protected Cultivation technology (CPCT), ICAR-Indian Agricultural Research Institute, New Delhi. Based on 16S rRNA sequences, IRh9, IRh10, and IRh15 showed > 98% homology with Bacillus licheniformis, Priestia megaterium and Pseudomonas putida, respectively. Compared to the control, the penetration of root-knot nematode in tomato roots was reduced by >50% under pot conditions through inoculation of these bacteria. Characterization through gas chromatography-mass spectrometry analysis revealed 30 different volatile organic compounds from these rhizobacteria. Among them, 19 compounds were identified from P. megaterium IRh10, followed by 16 compounds each from B. licheniformis IRh9 and P. putida IRh15. Furthermore, among the detected volatile organic compounds, acetic acid, hexadecane, hexadecanoic acid, octadecanoic acid, 1-decene and 9-octadeconoic acid are reported to possess nematicidal properties. Additional characterization of plant growth promotion traits associated with these rhizobacteria revealed that P. megaterium IRh10 and P. putida IRh15 produced indole acetic acid, while B. licheniformis IRh9 and P. megaterium IRh10 produced ammonia, but only P. putida IRh15 could solubilize the tricalcium phosphate under laboratory conditions. Among the 35 substrates studied, P. megaterium IRh10 utilized most (12), followed by B. licheniformis IRh9 and P. putida IRh15, which were able to use 11 and 8 substrates, respectively. The study showed that B. licheniformis IRh9, P. megaterium IRh10 and P. putida IRh15 are potential candidates for combating M. incognita infestation in tomato crops.